Investing in health for economic development: The case of Mexico - Nora Lustig (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Health is an asset with an intrinsic value as well as an instrumental value. Good health is a source of wellbeing and highly valued throughout the world. Health is not only the absence of illness, but capacity to develop a person's potential. Health is also an important determinant of economic growth. Given the importance of health, both as a source of human welfare and a determinant of overall economic growth, the Popular Health Insurance (Seguro Popular) was first introduced in Mexico as a pilot programme by the federal government in 2001, becoming part of the formal legislation in 2003. This study looks at the current situation, and some of the early findings and improvements made so far with regard to public health coverage in Mexico. – health ; healthcare ; poverty ; determinants of economic growth ; MDGs
Keywords: I12; I18; H51; 330; Gesundheit; Gesundheitspolitik; Wirtschaftswachstum; Armut; Mexiko